Transformasi Limbah Bambu Cendani menjadi Casing Ponsel Estetik Bergaya Etnik-Modern sebagai Upaya Mengangkat Produk Lokal melalui Inovasi Berkelanjutan - Mila Ariyani; Rifatun Hasanah; Y Yazid; Sri Jumini (CATHA SAINTIFICA, 2025)
The increasing public awareness of environmentally friendly products has driven the demand for mobile phone accessories that are not only functional but also have aesthetic value and cultural identity. This research aims to produce an innovative eco-friendly mobile phone casing product called CENDARIA, which combines ethnic-modern style with the use of cendani bamboo waste as the main material. The methods used include identifying potential local raw materials, designing ethnic-modern designs, prototyping, product quality testing, and disseminating the development results. The results show that cendani bamboo waste can be processed into a mobile phone casing with adequate structural strength, a unique visual appearance, and high aesthetic value, making it a competitive alternative to plastic casings. This innovation proves that the transformation of local waste can produce value-added products that support environmental sustainability while strengthening cultural identity. CENDARIA has an economic impact by creating business opportunities for local craftsmen and providing environmentally friendly product choices for consumers. CENDARIA can be a model for developing creative products based on local resources that contribute to waste reduction, economic empowerment, and a sustainable lifestyle.